Remote Colorimetric and Structural Diagnosis by RGB-ITR Color Laser Scanner Prototype. (3rd April 2012) - Guarneri, Massimiliano; Ferri de Collibus, Mario; Fornetti, Giorgio; Francucci, Massimo; Nuvoli, Marcello; Ricci, Roberto
Abstract : Since several years ENEA's Artificial Vision laboratory is involved in electrooptics systems development. In the last period the efforts are concentrated on cultural heritage remote diagnosis, trying to develop instruments suitable for multiple purposes concerning restoration, cataloguing, and education. Since last five years a new 3D (three-dimensional) laser scanner prototype (RGB-ITR) based on three amplitude-modulated monochromatic laser sources mixed together by dichroic filters is under development. Five pieces of information per each sampled point (pixel) are collected by three avalanche photodiodes and dedicated electronics: two distances and three target reflectivity signals for each channel, red, green, and blue. The combination of these pieces of information opens new scenarios for remote colorimetry allowing diagnoses without the use of scaffolds. Results concerning the use of RGB-ITR as colorimeter are presented.